Who was Sally Ride? - Stine, Megan; Hammond, Ted (New York : Grosset & Dunlap, 2013)
Looks at the life and career of the physician and NASA astronaut who became the first American woman in space in 1983.
800L
Keywords: Ride, Sally; United States. -- National Aeronautics and Space Administration; United States. -- National Aeronautics and Space Administration; Women astronauts -- United States; Astronauts -- United States; Women physicists -- United States; Astronauts; Physicists; Women